Esaform 2021 2021
DOI: 10.25518/esaform21.574
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of an induction heating process and resulting material distribution of a hybrid semi-finished product after impact extrusion

Abstract: Multi-material solutions offer benefits, as they, in contrary to conventional monolithic parts, are customised hybrid components with properties that optimally fit the application locally. Adapted components offer the possibility to use high strength material in areas where external loads require it and substitute them by lightweight material in the other areas. The presented study describes the manufacturing of a hybrid shaft along the process chain Tailored Forming, which uses serial pre-joined semi-finished… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
(12 reference statements)
0
4
0
Order By: Relevance
“…Previous studies have shown that temperature control is of particular importance for the forming of hybrid steel-aluminium semi-finished products. Therefore, an inhomogeneous temperature field is set via induction heating [7]. The aim is to heat the steel as much as possible and keep the aluminium as cold as possible, to match the flow stresses of both materials.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that temperature control is of particular importance for the forming of hybrid steel-aluminium semi-finished products. Therefore, an inhomogeneous temperature field is set via induction heating [7]. The aim is to heat the steel as much as possible and keep the aluminium as cold as possible, to match the flow stresses of both materials.…”
Section: Methodsmentioning
confidence: 99%
“…Thermal material data was defined based on Simufact Forming 16 database. The relative permeability was determined by Behrens et al using the method described in [7]. The calculated inhomogeneous temperature field after induction heating is transferred to the semi-finished product of the impact extrusion model.…”
Section: Fig 2 Flow Curves For Various Temperatures and A Strain Rate...mentioning
confidence: 99%
“…For an adequate numerical investigation of an induction heating process, the electromagnetic material data of the materials used are crucial. The required material properties for the 100Cr6 were taken from previous work [9]. Boundary conditions like current in the induction coil and the frequency were derived from experimental inductive heating tests, which are described in detail in [7].…”
Section: Methodsmentioning
confidence: 99%
“…Steel and titan require forging temperatures that exceed the melting temperature of aluminium. To prevent melting of the aluminium, which destroys the component, special heating strategies were developed for several hybrid components [4,5]. The heating takes place locally using induction heating.…”
Section: Introductionmentioning
confidence: 99%